Variation of Displacement Fields for Great Earthquakes due to Rectangular Fault System - Yadav, Ramhit (Orchid Academia Siraha, 2022)
The expressions for the displacement fields produced by a finite rectangular fault associated with great earthquakes are explained by elastic theory of dislocation. The variation of displacement fields has been estimated by considering the elastic half-space in contact with traction free boundary and varying depth, distance from top to bottom of the fault. It is also carried out in an infinite elastic medium. Also, the variation of displacement fields with the distance from fault especially for strike slip fault shows that even if different fault length and approximately equal magnitudes, the variation of displacement fields with the distance from the fault is almost the same in the case of great earthquakes viz. San Francisco (1906) and Bihar-Nepal (1934).